Advancing firms performance in Ghana: does IFRS adoption matter?. (3rd December 2020) - Appiah, Kingsley Opoku; Gyimah, Prince; Adom, Michael Boachie
This study examines whether the transition of local GAAP to IFRS affects listed firms in the Sub-Saharan Africa region. Using binary logistic regression on the dataset from Ghana, we find that profitability and liquidity reduced during the official adoption fiscal year of IFRS but not, earning management. We also find that growth and leverage increase during financial reportage for the post-adoption period of IFRS. We conclude that the adoption of IFRS leads to more value relevant accounting measures in developing country context. Our study is one of first of its kind to investigate the effect of pre-and-post adoption of IFRS in Ghana using accounting measures, implying the study's finding does not only contribute to the literature, but also policy and practice.